2022
DOI: 10.3390/su142013669
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strength of Saline Sandy Soils Stabilized with Alkali-Activated Cements

Abstract: Saline soils usually cannot satisfy the requirements of engineering projects because of their inappropriate geotechnical properties. For this reason, they have always been known as one of the problematic soils worldwide. Moreover, the lack of access to normal water has intensified the use of saline water resources such as seawater in many construction and mining projects. Although cement stabilization is frequently used to improve the engineering properties of saline soils, Portland cement’s usage as a binder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…On the other hand, in a steam-curing environment, the steam kept the shrinkage process from drying up, preserving the samples' strength. The results of this study contributed to the potential of using seawater as well as sea sand in the manufacture of geopolymer concretes [2,[17][18][19].…”
Section: Introductionmentioning
confidence: 72%
“…On the other hand, in a steam-curing environment, the steam kept the shrinkage process from drying up, preserving the samples' strength. The results of this study contributed to the potential of using seawater as well as sea sand in the manufacture of geopolymer concretes [2,[17][18][19].…”
Section: Introductionmentioning
confidence: 72%
“…The physical improvements of salinealkali soil mainly include land leveling, soil improvement in micro areas, soil loosening, alternate wet and dry cultivation and soil surface coverage [5,6]. The chemical improvements refer to the transformation, adsorption or fixation of saline-alkali components in the soil through the application of chemical modifiers and organic matter [7,8] to reduce the contents of saline-alkali components in the soil. For example, the cation exchange capacity of saline-alkali soil is improved by using corn straw biochar to increase the contents of organic matters and nutrients in the saline-alkali soils [9].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have studied the properties of alkali-activated slag and fly ash [ 33 , 34 ]. Reza et al [ 35 ] studied the effects of NaCl on the microstructure and mechanical properties of stabilized sandy soil with alkali-lithium-activated ash slag and confirmed that the alkali-lithium-activated slag could replace Portland cement for soil stabilization engineering in saline-alkali environments. Hania et al [ 36 ] investigated the potential of alkali-active powdered blast furnace slag and volcanic ash as green binders in clay stabilization projects.…”
Section: Introductionmentioning
confidence: 99%